2018
DOI: 10.18174/464051
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of whole effluent toxicity with substance based hazard of produced water discharged by Norwegian platforms

Abstract: At the beginning of the millennium OSPAR policy on produced water discharges focused on oil in water and the application of Best Available Technique (BAT) and Best Environmental Practice (BEP) associated with oil. In 2009 the OSPAR Offshore Industry Committee (OIC) agreed to set up an Intersessional Correspondence Group on development of a risk-based approach (RBA) for the management of produced water discharges (ICG-RBA), with the task of developing a proposal for a holistic approach for the management of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In a similar study by M. Reed et al (1996), organic acids and aliphatic hydrocarbons were found to be the main drivers of PW ecotoxicity. In a study by de Vries and Jak (2018) covering PW from 25 platforms in the North Sea, aliphatic hydrocarbons, organic acids, and PCs were found to be the biggest contributors, while the contributions of phenols and PAHs were negligible. A similar study of 12 platforms in the Bass Strait found sulfide, aromatic hydrocarbons, and ammonia to be the main ecotoxicity drivers and cyanide, metals, and phenols to be negligible (Parkerton et al, 2018).…”
Section: Hazard Assessment Of Pw In the Rbamentioning
confidence: 94%
See 3 more Smart Citations
“…In a similar study by M. Reed et al (1996), organic acids and aliphatic hydrocarbons were found to be the main drivers of PW ecotoxicity. In a study by de Vries and Jak (2018) covering PW from 25 platforms in the North Sea, aliphatic hydrocarbons, organic acids, and PCs were found to be the biggest contributors, while the contributions of phenols and PAHs were negligible. A similar study of 12 platforms in the Bass Strait found sulfide, aromatic hydrocarbons, and ammonia to be the main ecotoxicity drivers and cyanide, metals, and phenols to be negligible (Parkerton et al, 2018).…”
Section: Hazard Assessment Of Pw In the Rbamentioning
confidence: 94%
“…This suggests that the multiphase characteristics of PW make it difficult to conduct the standard ecotoxicity tests on the mixture, especially long‐term tests. This is also highlighted by the difficulty of meeting validity criteria of standard ecotoxicity testing when testing PW, as reported by de Vries and Jak (2018). In their standardized ecotoxicity tests of PW from 25 platforms, 20 tests met the validity criteria defined in the ISO test for Vibrio fischeri , but only 11 and 10 met those of Acartia tonsa and Skeletonema constatum tests, respectively.…”
Section: Challenges and Recommendations For Improved Hazard Assessmen...mentioning
confidence: 95%
See 2 more Smart Citations
“…When the latter database did not contain information on a required substance (group) the inter‐species correlation estimate was used. Because data on PAHs are scarce and variable (De Vries & Jak, 2018), EC50 data from the databases above were supplemented with information from Verbruggen (2012).…”
Section: Methodsmentioning
confidence: 99%